Kelas Menengah Perubah “Sebuah Kontestasi Stratifikasi Dominasi Dalam Kapitalisme dan Konsumerisme” (Dalam Perspektif Teori Sosio HistorisKritis C. Wright Mills) - Arie Wahyu Prananta (DIMENSI - Jurnal Sosiologi, 2015)
Study and Discussion Middle Class in Indonesia Since the 1970's making us Startled and remind them a very central role in the class structure of the elite class and the lower class. Mengah class structure that is very dynamic and became the most influential class in the class structure Indonesia1 nation. The most influential class of bargaining structure makes it difficult to track class in the class structure of the Indonesian nation but their role is very important, and some of the events changes ranging from the collapse of the old order and the new order and the new order to the order of the reform to make the lesson for the nation that etintas and their role is to make the power of change in the state system and social structure in the community. Vagueness figure mengah class in the social structure in the community make this a decent middle-class researched and chosen as a topic there does require quite a lot of study and also an imagination in soiologi to be in perspektifkan and projected in an empirical object assumes constructed reality of objects material to be appointed as a more macro assumptions preposition. The existence of vague mengah class does not mean the absence of middle class structures etintas them, the emergence of class roles mengah be a force of change in a country makes them very central role, classification and categorization within a social structure in the community is very vague, so the need to study very deep study and empirically focused on middle-class structure, Refine concepts in a theory of the middle class by Ariel Hariyanto in a study Robinson is the middle class are some government officials, practitioners, managers in a company fund or class of educated intellectual, in the structure existing social Indonesian nation. Capitalism here as in imagine a production order in the capital penguasaaan. The need for this level of precision and mapping of capitalism in the frame in the ownership of capital.